UWB pulse generation,shaping and analysis - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
The linear systcm characteri7,/ltioo lind calibrntion relies substantially on the detennination of their pulse response. Instrument performance and its compensation for non-linear behavior of the system can be made by knowing the pulse response of the instrument. e.g. the digital oscilloscope pulse response can be used to detennioe aTKI characTerize its shon pulse response[2J. In TDR systemS the shon pulse generators are used 10 characterize long distant:e transmission lines and 10 detect open (or short) circuit faults cxisting over thc lines. By analyzing pulse reflections, one can use this reflcctomcntory for cstimation of signal parameters such as change in impedance, length of the line, time delay caused arwJ pulse dispersion WiTh high accuracy 131.Another application area for short-pulse generation is UWB systems. where sub-nanrn;ccond pulse generation is of inTerest by researchers. In the case of UWB pulses used for response evaluation, the information provided is in more detail as the resulting frequency components' responses are extensive and more elaborative. Federal Communications Commission (FCC) while discussing rules for communication in ils repon defines a UWB system as :In unlicensed frequency spectrum ranging over 1, 500 MHZ spreading over frcqucncy baTKI l1lllging from 3.IGHz to IO.6GHz [4]. The origin of UWB technolOgy daTes back TO the early 1960s from its application view point in electromagnetic. After sevcral years of Technological advancement, UWB systems have been used in several applications already elaborated in [5].